Denning phenology of polar bears (Ursus maritimus) in the Barents Sea population - Sulich, Joanna Maria (UiT Norges arktiske universitet, 2019)
Timing reproductive effort to match food availability is important due to high energetic costs of reproduction. Female polar bears need sufficient time in the den to nurse cubs until they are big enough to withstand the Arctic environment, however females’ emergence from the den needs to be synchronized with ringed seal pupping peak, which is a crucial energy source for polar bears. The phenology of polar bear maternity denning may shift over time due to changing environmental conditions. Denning phenology of polar bears from Barents Sea population (BS) from 2011 to 2017 was detected using satellite telemetry GPS locations, temperature and activity data. This resulted in full length records of 29 maternity denning events, with estimated dates of entry and emergence. This study found that 64 % (0.49-0.78, n=45) of all reproductively available females went into den. Additionally, 15 % (0.04-0.35, n=26) of females initially accompanied by cubs of the year and 11 % (0.00-0.48, n=9) of females accompanied by yearlings went into den following autumn, possibly due to early loss of cubs which allowed for subsequent mating and denning. Females started denning between Oct 4th and Jan 5th, mean Nov 5th (SD=29 [Oct 7th - Dec 4th], n=35), and emerged from it from Dec 12th to May 1st, mean Mar 14th (SD=32 [Feb 10th – Apr 15th], n=29). Bears entering den later in the year denned for a shorter period. Den emergence dates were less variable than den entry dates, which supports the hypothesis that bears time den emergence to the peak seal pup availability. Additionally, young females were less likely to go into den and if denning, they emerged from den earlier, possibly due to reproductive failure. Warmer weather in spring, indicated by negative Arctic Oscillation Index values, was associated with later den entry, suggesting that spring conditions potentially influence polar bears hunting success and may play a role in collecting energy stores to undertake successful maternity denning.